AUTOMATIC PLANT WATERING PROTOTYPE AND RAT REPELLENT ON EGGPLANT - Elvina, Elvina; Gianadevi, Fettiana; Lolita, Baby; Iriana, Revida; Fathulloh, Shafwan Aji (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Water is the main constituent of plant cells. Eggplant plants include plants that are not drought tolerant, but also not resistant to standing water. In addition, eggplant is also susceptible to rat pests. Most farmers in Indonesia still use the manual method, sometimes when using the manual method it can lead to negligence in watering plants and guarding against rat pests. The use of mechanization tools is needed to facilitate and overcome negligence that can occur at any time, which can help plant cultivation by getting the best results, overcoming negligence that can cause losses, and damage to plants. In this tool there are several components of input, process, and output. Input section consists of 3 sensors, namely, Soil Moisture, Passive Infra Red, and DHT 11. Process section there is only Arduino Uno. And the output section consists of 4 components, namely water pump, LCD, buzzer, and servo. Automatic watering works when the value of the Soil Moisture sensor is more than 700 which means it is dry, and the water pump will turn on until the value is less than 700. The mouse repellent works when the PIR sensor detects the movement of an infrared object and will move the Servo and Buzzer.